Museum Gastronomi Indonesia Virtual Sebagai Destinasi Wisata Edukasi, Sejarah dan Hiburan - Riyanto, Wisnu; Rahmanita, Myrza; Wulan, Saptarining (Universitas Pendidikan Indonesia, 2023)
ABSTRACTGastronomy museums have three dimensions that must be fulfilled and become the values sought by museum visitors as tourist attractions, namely the dimensions of education, history, and entertainment. The Virtual Indonesian Gastronomy Museum (MGI Virtual) is a gastronomic museum in Indonesia which has been opened to the public in 2021. This research aims to analyze the potential of MGI Virtual as an educational, historical and entertainment tour according to the dimensions of a gastronomic museum. This research is classified as a descriptive quantitative research with data taken from 80 respondents who are MGI Virtual visitors with domiciles in DKI Jakarta. The results of the study stated that visitors enjoyed MGI Virtual more as an educational and historical tour, while the rating for entertainment tourism was still relatively low. To increase the entertainment dimension in MGI Virtual, it can be done by developing technology and features that are more interactive and attract visitors so that they get a pleasant and memorable visiting experience.ABSTRAKMuseum gastronomi memiliki tiga dimensi yang harus terpenuhi dan menjadi nilai yang dicari oleh pengunjung museum sebagai tempat wisata yaitu dimensi edukasi, sejarah, dan hiburan. Museum Gastronomi Indonesia Virtual (MGI Virtual) merupakan museum gastronomi di Indonesia yang telah dibuka untuk umum pada tahun 2021. Penelitian ini bertujuan untuk menganalisis potensi MGI Virtual sebagai wisata edukasi, sejarah, dan hiburan sesuai dengan dimensi museum gastronomi. Penelitian ini tergolong dalam penelitian kuantitatif deskriptif dengan data yang diambil dari responden berjumlah 80 orang yang merupakan pengunjung MGI Virtual dengan domisili di DKI Jakarta. Hasil penelitian menyatakan bahwa pengunjung lebih menikmati MGI Virtual sebagai wisata edukasi dan sejarah, sedangkan penilaian untuk wisata hiburan masih tergolong rendah. Untuk meningkatkan dimensi hiburan pada MGI Virtual dapat dilakukan dengen mengembangkan teknologi dan fitur yang lebih interaktif dan menarik pengunjung sehingga mendapatkan pengalaman berkunjung yang menyenangkan dan berkesan.